Florida’s Harmful Algal Bloom (HAB) Problem: Escalating Risks to Human, Environmental and Economic Health With Climate Change - Heil, Cynthia Ann; Muni-Morgan, Amanda Lorraine (Frontiers in Ecology and Evolution, 2021)
Harmful Algal Blooms (HABs) pose unique risks to the citizens, stakeholders, visitors, environment and economy of the state of Florida. Florida has been historically subjected to reoccurring blooms of the toxic marine dinoflagellate Karenia brevis (C. C. Davis) G. Hansen & Moestrup since at least first contact with explorers in the 1500’s. However, ongoing immigration of more than 100,000 people year–1 into the state, elevated population densities in coastal areas with attendant rapid, often unregulated development, coastal eutrophication, and climate change impacts (e.g., increasing hurricane severity, increases in water temperature, ocean acidification and sea level rise) has likely increased the occurrence of other HABs, both freshwater and marine, within the state as well as the number of people impacted by these blooms. Currently, over 75 freshwater, estuarine, coastal and marine HAB species are routinely monitored by state agencies. While only blooms of K. brevis, the dinoflagellate Pyrodinium bahamense (Böhm) Steidinger, Tester, and Taylor and the diatom Pseudo-nitzschia spp. have resulted in closure of commercial shellfish beds, other HAB species, including freshwater and marine cyanobacteria, pose either imminent or unknown risks to human, environmental and economic health. HAB related human health risks can be classified into those related to consumption of contaminated shellfish and finfish, consumption of or contact with bloom or toxin contaminated water or exposure to aerosolized HAB toxins. While acute human illnesses resulting from consumption of brevetoxin-, saxitoxin-, and domoic acid-contaminated commercial shellfish have been minimized by effective monitoring and regulation, illnesses due to unregulated toxin exposures, e.g., ciguatoxins and cyanotoxins, are not well documented or understood. Aerosolized HAB toxins potentially impact the largest number of people within Florida. While short-term (days to weeks) impacts of aerosolized brevetoxin exposure are well documented (e.g., decreased respiratory function for at-risk subgroups such as asthmatics), little is known of longer term (>1 month) impacts of exposure or the risks posed by aerosolized cyanotoxin [e.g., microcystin, β-N-methylamino-L-alanine (BMAA)] exposure. Environmental risks of K. brevis blooms are the best studied of Florida HABs and include acute exposure impacts such as significant dies-offs of fish, marine mammals, seabirds and turtles, as well as negative impacts on larval and juvenile stages of many biota. When K. brevis blooms are present, brevetoxins can be found throughout the water column and are widespread in both pelagic and benthic biota. The presence of brevetoxins in living tissue of both fish and marine mammals suggests that food web transfer of these toxins is occurring, resulting in toxin transport beyond the spatial and temporal range of the bloom such that impacts of these toxins may occur in areas not regularly subjected to blooms. Climate change impacts, including temperature effects on cell metabolism, shifting ocean circulation patterns and changes in HAB species range and bloom duration, may exacerbate these dynamics. Secondary HAB related environmental impacts are also possible due to hypoxia and anoxia resulting from elevated bloom biomass and/or the decomposition of HAB related mortalities. Economic risks related to HABs in Florida are diverse and impact multiple stakeholder groups. Direct costs related to human health impacts (e.g., increased hospital visits) as well as recreational and commercial fisheries can be significant, especially with wide-spread sustained HABs. Recreational and tourism-based industries which sustain a significant portion of Florida’s economy are especially vulnerable to both direct (e.g., declines in coastal hotel occupancy rates and restaurant and recreational users) and indirect (e.g., negative publicity impacts, associated job losses) impacts from HABs. While risks related to K. brevis blooms are established, Florida also remains susceptible to future HABs due to large scale freshwater management practices, degrading water quality, potential transport of HABs between freshwater and marine systems and the state’s vulnerability to climate change impacts.